PEMETAAN DIGITAL DAN PENANAMAN MANGROVE SEBAGAI UPAYA KONSERVASI BERKELANJUTAN DI EKOWISATA MANGROVE WONOREJO SURABAYA - Kholid, Ikhwan; Rithmaya, Chitra Laksmi; Kartik, Titis Puspitaningrum Dewi; Hapsari, Indah; Trikumala, Nabila; Rahmadhani, Anisa (Universitas Mataram, 2025)
Awareness of the importance of planting and preserving mangrove forests, especially in nature conservation and land rehabilitation activities, is certainly important. Sustainable conservation not only supports nature conservation, but also has an impact on local economic sustainability. Sustainable management is an effort to care for, protect, and preserve nature and the surrounding environment. Moreover, sustainable conservation emphasises the sustainable use of nature and the environment, both for the present and future generations. This activity was conducted at the Mangrove Tourism Site in Wonorejo Timur Village, Rungkut District, Surabaya. The event was attended by a team of lecturers, students, and mangrove managers (Non-Governmental Organisation). The method of implementing this activity involved observation (identifying partner needs), obtaining solutions, offering solutions, reaching an agreement on solutions, coordination, educating visitors, and evaluating the activity. From the pre- and post-test results, the average pre-test score was 6.19, while the post-test score was 7.65, showing a significant increase. When considering the average increase from pre-test to post-test, there was a 1.46-point increase. This indicates that through education on tree planting and digital mapping, students were able to understand the key points presented in this activity and demonstrated improved knowledge of Artificial Intelligence, specifically the ability to create barcodes.